Ecolingüística y ecogramática: repensar la interrelación entre lengua, sociedad y ecosistema. El caso de los animales en artículos periodísticos de Argentina - Günther, Nazira B. (Pontificia Universidad Católica del Perú, 2022)
In this paper, we briefly characterize ecolinguistics as a discipline. Then, from the contributions of the Systemic-Functional theory proposed by Halliday (1990; 2004) we reformulate concepts from Supisiche (2019) and from Stibbe's (2020) story-based perspective to analyze the discursive construction of animals in a corpus of fragments of five journalistic news items taken from two online newspapers in Argentina (Infobae and Clarín). In this way, we compare how they construct the non-human animal in their statements and how these constructions reveal and influence the stories we make about these beings and our relationship with them. Our findings indicate that the analysis of the lexical-grammatical structure reveals discursive elements typical of stories destructive to the environment and animals, which reproduce ideologies and evaluations that place humans in a superior hierarchical position with respect to the latter.

En este trabajo, realizamos una breve caracterización de la ecolingüística como disciplina. Luego, a partir de los aportes de la teoría Sistémico-Funcional propuesta por Halliday (1990; 2004) retomamos y reformulamos conceptos de Supisiche (2019) y de la perspectiva basada en historias de Stibbe (2020) para analizar la construcción discursiva de los animales en un corpus de fragmentos de cinco noticias periodísticas tomadas de dos diarios online de Argentina (Infobae y Clarín). De esta forma, comparamos cómo construyen al animal no humano en sus enunciados y cómo esas construcciones revelan e influyen en las historias que nos hacemos sobre estos seres y en nuestra relación con ellos. Nuestros hallazgos indican que el análisis de la estructura léxico-gramatical revela elementos discursivos propios de historias destructivas para el ambiente y los animales, las cuales reproducen ideologías y evaluaciones que colocan al ser humano en una posición jerárquica superior con respecto a estos últimos.
Ecolinguistics and ecogrammar: rethinking the interrelationship between language, society, and ecosystem. The case of animals in newspapers articles in Argentina
Keywords: Ecolinguistics; Ecogrammar; Discourse analysis; Animals; Ecogramática; Ecolingüística; Análisis del discurso; Animales; https://purl.org/pe-repo/ocde/ford#6.02.06